2006
DOI: 10.1002/mrm.20805
|View full text |Cite
|
Sign up to set email alerts
|

Robust analysis of short echo time 1H MRSI of human brain

Abstract: Short echo time proton MR Spectroscopic Imaging (MRSI) suffers from low signal-to-noise ratio (SNR), limiting accuracy to estimate metabolite intensities. A method to coherently sum spectra in a region of interest of the human brain by appropriate peak alignment was developed to yield a mean spectrum with increased SNR. Furthermore, principal component (PC) spectra were calculated to estimate the variance of the mean spectrum. The mean or alternatively the first PC (PC 1 ) spectrum from the same region can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…More advanced techniques consist of subtracting a modeled macromolecular signal in the frequency domain from the original spectrum. Models may be generated with wavelets [71,132,133,95,75] or splines [134]. A comparison between wavelets and splines has been done in [130] but no significant differences have been found.…”
Section: 321mentioning
confidence: 99%
“…More advanced techniques consist of subtracting a modeled macromolecular signal in the frequency domain from the original spectrum. Models may be generated with wavelets [71,132,133,95,75] or splines [134]. A comparison between wavelets and splines has been done in [130] but no significant differences have been found.…”
Section: 321mentioning
confidence: 99%
“…Although a number of past studies have examined the reproducibility or reliability of 1 H‐MRSI (12–20), most have been based on few subjects, some were conducted with nonstandard pulse sequences, and none have been conducted at 3T using a short TE. Furthermore, the majority of these studies were not based on data corrected for partial volume effects, nor has a consistent interscan interval or measure of reproducibility or reliability been applied across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the majority of these studies were not based on data corrected for partial volume effects, nor has a consistent interscan interval or measure of reproducibility or reliability been applied across studies. Only two studies (13, 16) used a standard measure of test‐retest measurement reliability, the intraclass correlation coefficient (ICC), while two others (12, 14) used an analysis of variance approach to calculate coefficients of variation (CVs) as a measure of reproducibility, dividing the square root of separated variance components (for subject, scan, or voxel) by the mean across all voxels. The remainder of the studies reported more conventional CVs, based on the means and standard deviations of metabolite intensities over similar voxels across subjects or repeated scans.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 In the present study, we used RCMS to determine regional and gray/white matter variations of mI and other metabolites, including NAA, and creatine (Cr) in AD and in cognitively normal (CN) elderly subjects.…”
mentioning
confidence: 99%